Effect of compaction degree on the soil-water characteristic curve of dam impervious soil: model comparison and microstructural analysis - Li, Xuemei; Li, Ke; Jiao, Xiuming; Chi, Yunfei; Yue, Xiu (Frontiers in Earth Science, 2025)
The matric suction of three types of dam impervious soils (HZ, ZJ, and WY) was measured during drying-wetting cycles under various compaction degrees using the filter paper method. The soil-water characteristic curves (SWCCs) were fitted using the van Genuchten (VG) model and the Fredlund-Xing (FX) model. Based on the fitting parameters, the water retention characteristics of the impervious soils were evaluated. Combined with particle size distribution curves and scanning electron microscopy (SEM) images, the influence mechanism of compaction degree on water retention was investigated from a microstructural perspective. The results show that: (1) The filter paper method revealed distinct suction–water content behaviors across soil types and compaction levels. The HZ soil showed the lowest air-entry value (AEV) and highest sensitivity to compaction, while WY soil maintained strong water retention and minimal variation in SWCC, indicating structural stability. (2) The VG model consistently outperformed the FX model in fitting the SWCCs of all three soils, with all R2 values exceeding 0.95. VG provided more stable parameter trends (a, n) and better captured the influence of compaction on hysteresis, especially for fine-grained soils. (3) SEM images and particle size distribution analyses confirmed that WY and ZJ soils possess higher clay content, denser particle arrangements, and smaller pores, contributing to stronger water retention. In contrast, the sandier HZ soil exhibited coarser pores, more significant structural rearrangement under compaction, and an increased presence of ink-bottle pores, intensifying the hysteresis effect. This study reveals the microstructural mechanism through which particle size composition and compaction degree jointly regulate the water retention properties of dam impervious soils, providing a basis for unsaturated seepage analysis and seepage control design in earth-rock dams.